Chemical composition, acaricidal and insecticidal effects of essential oil from Achillea filipendulina against two arthropod pests; Oryzaephilus surinamensis and Tetranychus urticae. (3rd April 2017) - Ebadollahi, Asgar
Abstract: A significant toxicity of essential oil isolated from Achillea filipendulina Lam. was realized against two arthropod pests: Oryzaephilus surinamensis (L.) and Tetranychus urticae Koch. Probit analysis revealed LC50 values were 12.121 (10.366 ± 15.235) and 6.043 (5.018 ± 7.564) μl/l air for O. surinamensis and T. urticae, respectively. Essential oil analysis indicated geraniol (36.95%), borneol L (9.58%), 1, 8-cineole (5.98%) and copaene were the major components. According to the results of present work, the terpene-rich essential oil of A. filipendulina can be considered as a safe alternative to the synthetic chemicals in the management of O. surinamensis and T. urticae .